Ketamine Alleviates Postoperative Depression-Like Symptoms in Susceptible Mice: The Role of BDNF-TrkB Signaling - Li, Shan; Luo, Xiaoxiao; Hua, Dongyu; Wang, Yue; Zhan, Gaofeng; Huang, Niannian; Jiang, Riyue; Yang, Ling; Zhu, Bin; Yuan, Xianglin; Luo, Ailin; Yang, Chun (Frontiers in Pharmacology, 2020)
Patients are more likely to suffer from central nervous system (CNS) complications after anesthesia and surgery. However, postoperative depression (POD) has not yet received sufficient attentions, and its pathogenesis and therapeutic strategies remain poorly understood. We here aimed to investigate whether brain derived neurotrophic factor (BDNF)-tropomyosin-related kinase B (TrkB) signaling plays an important role in POD. BDNF-TrkB signaling was altered in brain and peripheral tissues, including medial prefrontal cortex (mPFC), hippocampus, liver and muscle, among control, POD susceptible and resilient groups. Additionally, we demonstrated that 7,8-dihydroxyflavone (7,8-DHF), a TrkB agonist, could exert its pharmacologic property to alleviate POD-like symptoms. More importantly, ketamine, a non-competitive N-methyl-D-aspartic acid (NMDA) receptor antagonist, also has significant antidepressant effects in POD model, associating with the improving effects on levels of BDNF-TrkB signaling in brain and peripheral tissues. Interestingly, the beneficial effects of ketamine on POD-like symptoms are fully attenuated by a TrkB antagonist. These findings suggest that abnormal expressions of BDNF-TrkB signaling in brain and peripheral tissues are implicated in the pathogenesis of POD, and that therapeutic agents targeting BDNF-TrkB, particularly ketamine, could favor the beneficial effects for POD.